INTENSI MENYEBARKAN BERITA PALSU DITINJAU DARI MODEL KEPRIBADIAN LIMA BESAR PADA MAHASISWA PSIKOLOGI - Gumgum Gumelar; Erik Erik; Muhammad Alfatih Robbany (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2019)
This research was conducted to determine whether personality dimensions in big five personality model influence the intention to spread false news on students of Psychology Department, Faculty of Psychology Education, Jakarta State University. Some results of previous studies show that personality dimensions in the five major personality models have a significant relationship with the intention to spread false news. The research data was taken using survey method with questionnaire technique involving 161 subjects of students from the Department of Psychology, Faculty of Psychology Education, State University of Jakarta who were selected through simple random sampling method. Data analysis was carried out using multiple linear regression analysis techniques. The analysis shows that only extraversion and neuroticism personality dimensions have a significant effect on the intention to spread false news, while openness (to experience), conscientiousness, and agreeableness of personality dimensions have no significant influence on the intention to spread false news